Gold and REE pre-enrichment in metasomatized Archean lithospheric mantle aided the genesis of Mesozoic giant ore deposits, eastern North China Craton - Shan-Shan Li; Kun-Feng Qiu; Timothy Kusky; Lu Wang; Hartwig E. Frimmel; Yi-Xue Gao; Tong Zhou; Deng-Yang He; Hao-Cheng Yu; Zheng-Yu Long; Tian-Shuo Liang; Ying-Jiu Wang; et al. (Earth-Science Reviews, 2026)

Hybrid cultured meat as an integrated food production system: Recent advances and commercialization challenges - ChanJin Kim; SoHee Kim; Da Young Lee; Ermie Mariano; SiHoon An; Young-Hwa Hwang; Sun Jin Hur; Seon-Tea Joo (Food Research International, 2026)

Urban CO2 flux characteristics observed at an eddy-covariance tower in northeastern Seoul - Hyo-Been An; Ba-da Yeon; Seung-Bu Park (Atmospheric Environment, 2026)

A comparative analysis of regulatory frameworks and their market impacts on health functional foods: perspectives from South Korea, Canada, the United States, and China - Da-Eun Min; Dal Eum Han; Kwonsoo Kang; Ke Ding; Guangpeng Xu; Mi-Young Lee; Dong Sung An; Nayon Hur; Jin Man Kim; Ji Youn Hong; Bok Kyung Han; Martin J. T. Reaney; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

A hierarchical thermal preference structure for understanding satisfaction in multi-occupant offices under cooling season conditions - Jingjing An; Qixuan Li; MingYang Qian; Da Yan; Ruosa Wu; Xin Zhou (Building and Environment, 2026)

Integrating physiology, behavior, and transcriptomics to refine pesticide risk assessment: the case of flupyradifurone and Coccinella septempunctata - Yuxin Dong; Yajie Zhang; Boyang An; Wenqiu Yuan; Guy Smagghe; Qiuju Qin; Yunzhuan He; Da Wang (Journal of Pest Science, 2026)

Impact of land use transition on ecosystem services in the Yangtze River economic belt and associated mechanism - Youzhi An; Mengsha Fan; Zhihao Tao; Peng Zhao; Hualin Chen; Da Li; Yun Wu; Qiuju Wu; Jin Sun; Feng Xu; Fengtai Zhang (Environment, Development and Sustainability, 2026)

Redox homeostasis regulation during the formation of archeospores in Neopyropia yezoensis - Li-Fei Yang; An-Ran Shen; Da-Hai Gao (Algal Research, 2026)

Multidimensional dissection of shared genetic susceptibility in ulcerative colitis and colorectal cancer: novel insights from integrative single-cell and multi-omics analysis - Fanfan Zhu; Xin Yao; Da Liu; Shanshan Wang; Xuyu Huang; Jing Zhou; Song Wang; Shanneng Tang; Dongping Lai; Shuang Yang; Xiaobing Meng; Xinyue Zhang; et al. (Inflammation Research, 2026)

Dual-salt template synthesis of coal tar pitch-based porous carbon for capacitive deionization of NH4+ and NO3− - Ke Li; Luwei Miao; Weilong Xiao; Rencheng Li; Yang Bao; Yufeng Da; Xurui An; Qiulin Yang; Wenqing Chen (Desalination, 2026)

Microfluidic investigation on multiphase interaction behavior and carbon dissolution sequestration mechanisms during CO₂ injection in high-water-cut deep reservoirs - Xue Zhang; Qi’an Da; Chenxi Duan; Bin Huang; Cheng Fu; Dian Zhang; Lei Li; Yuliang Su (Chemical Engineering Journal, 2026)

Tm4sf19 inhibition alleviates imiquimod-induced psoriatic dermatitis by regulating inflammatory signaling pathways and keratinocyte proliferation in mice - Min Gi Kang; Sujin Park; Eunji Hong; Min-Jung Lee; Da Seul Jung; Jin Sun Heo; Haein An; Min Woo Kim; Naim Park; Hyeyeon Park; Pyunggang Kim; Minjung Son; et al. (Inflammation Research, 2026)

Energy-efficiency optimization of tunnel lighting systems: an adaptive penalty function model considering combined parameters of inner wall reflectivity and luminaire layout - Hao Liu; Shiyong He; Weidong Tang; Da Xu; Jia’an Niu; Xin Tang; Zhonglang Yang; Bo Liang (Tunnelling and Underground Space Technology, 2026)

Comprehensive understanding of new particle formation in China through advanced modeling - Jiewen Shen; Bin Zhao; An Ning; Wei Nie; Chao Yan; Yuyang Li; Runlong Cai; Alfonso Saiz-Lopez; Manish Shrivastava; Biwu Chu; Da Gao; Nanna Myllys; et al. (Science Bulletin, 2026)

Laboratory selection reveals flubendiamide resistance, fitness costs, and detoxification-related mechanisms in Spodoptera frugiperda: Insights for insecticide resistance management - Xiaoqi Wang; Peng Song; Boyang An; Guy Smagghe; Shipeng Han; Shanshan Feng; Qiuju Qin; Da Wang; Yunzhuan He (Pesticide Biochemistry and Physiology, 2026)

Multicolor vanadium dioxide-polyvinylpyrrolidone/silver bilayer smart films for reconfigurable visible color and solar energy modulation - Yoonjoo Choi; Byoungsu Ko; Hyungyoon Choi; Giyong Park; Sunga Kim; Ho Young Woo; Da Won Lee; Ran An; Yerin Kim; Sung-Hoon Hong; Junsuk Rho; Tianshuo Zhao; et al. (Chemical Engineering Journal, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Facile eco-friendly sol-gel synthesis of highly monodispersed Zn@silica nanospheres with dual antibacterial mechanism against multidrug-resistant bacteria - Yesul Jeong; Hyeran Kim; Soon Chang Lee; Ha-Rim An; Jong-Seong Bae; Yunju Choi; Byoungchul Son; Ji-In Park; Da-Hye Kim; Jiwon Seo; Eui-Jeong Han; Ji-Hyun Lee; et al. (Chemical Engineering Journal, 2026)

Downscaling prediction of urban wind environment based on PBMs and hybrid MLP-CNN model - Xiaohan Shen; Ruolan Sun; Gerui Sui; Rongmao Xu; Xin Zhou; Da Yan; Jingjing An (Urban Climate, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Polydeoxyribonucleotides isolated from the food fermentation strain Enterococcus faecium mitigate neuroinflammation via MAPK-mediated BMP/SMAD/Wnt regulation under neuro-oxidative stress - Da Hye Song; Yu-Rim Lee; Seung Min Yu; Soo Youn Lee; Sae-Hun Kim; Jeung Hee An (Food Bioscience, 2026)

Urban–rural differences in residential energy-use behavior and energy-saving awareness: Evidence from a Chinese megacity - Jingjing An; Tianyi Li; Chuang Wang; Da Yan; Shan Hu (Energy and Buildings, 2026)

Long-term impact of climate change on residential cooling loads in Beijing: A multi-factor analysis of occupant behaviors and envelopes - Jingjing An; Wenyan Liu; Chuang Wang; Xin Zhou; Shan Hu; Da Yan (Energy and Buildings, 2026)

Decoupling photocatalytic nitrogen activation: Broad-spectrum ammonia synthesis in pure water via attenuated hole oxidation dynamics in intrinsically active Bi2O2Se - Jiayu Gu; Chen Wei; Jinhao Xu; Xiu Zhang; Chunjie Zhu; Da Teng; Leyi Liu; Meizhi Lan; Wenjing An; Yingying Xu; Pengxiang Qiu; Shuxian Hu (Chemical Engineering Journal, 2026)

Analysis of pesticide residues in açaí-based food products: an approach using polymeric ionic liquid-based solid-phase microextraction coupled to gas chromatography–mass spectrometry - Luis Eduardo Silva Nascimento; Bhawana Thapa; Shu-An Hsieh; Plínio Ribeiro Rodrigues; Marcella Vitória Galindo; Wellington da Silva Oliveira; Helena Teixeira Godoy; Jared L. Anderson (Food Research International, 2025)

Receptor affinity-selective differential dynamics of membrane fusion initiation govern deltacoronavirus cross-species transmission - Da An; Qi Peng; Yong-Hao Ma; Wenguang Hong; Yi Pei; Shiyu Liu; Yan Li; Jizong Li; Yanke Shan; Yulong Yin; Bin Li; Fei Liu (Science China Life Sciences, 2025)

Araloside A Induces Raf/MEK/ERK-Dependent Autophagy to Mitigate Alzheimer’s and Parkinson’s Pathology in Cellular and C. elegans Models - Xue Chen; Xing-Yue Zhou; Cai Lan; Hai-Jun Fu; Zhi-Chao Li; Meng-Yi Chen; Yong-Ping Wen; Lu Yu; Da-Lian Qin; An-Guo Wu; Jian-Ming Wu; Xiao-Gang Zhou (Molecular Neurobiology, 2025)

The short-term and long-term effects of oil spill exposure on dyslipidemia: A prospective cohort study of Health Effects Research on the Hebei Spirit Oil Spill - Jiyoun Lee; Da-An Huh; Lita Kim; Kangyeon Park; Yun-Hee Choi; Se-Hyun Hwang; Woohyun Lim; Hyeon Jeong Choi; Kyong Whan Moon; Min-Sung Kang; Yong-Jin Lee (Marine Pollution Bulletin, 2025)

A new genus and species of Susumaniidae (Insecta: Phasmatodea) from the Middle Jurassic of Shaanxi Province, Northwest China - Qi-Ming Guo; Chun-Peng Xu; André Nel; An-Cheng Peng; Zhi-Gang Wen; Ting Li; Rui Fang; Da-Ran Zheng (Palaeoworld, 2025)

Molecular and microscale–level insights into the potential mobilization of toxic elements in Pb/Zn smelting contaminated soils under freeze–thaw cycles - Yu–Xiang Shi; Da–Mao Xu; Dong–Sheng Dai; Ze–Lin Xu; Bai–Hong An (Journal of Hazardous Materials, 2025)

Development and evaluation of cooling tower performance prediction using physics-informed neural networks - Zehongyu Kang; Xin Zhou; Da Yan; Jingjing An (Energy and Buildings, 2025)

Mitigating salt stress in cabbage: synergistic effects of nitric oxide donor GSNO and melatonin - Tran Hoang An; Nusrat Jahan Methela; Mohammad Shafiqul Islam; Da-Sol Lee; Meshari Winledy Msarie; Youn-Ji Woo; Bong-Gyu Mun; Moon-Sub Lee; Byung-Wook Yun (Plant Biotechnology Reports, 2025)

14-3-3 proteins: Multifunctional regulators in plants with new advances on arbuscular mycorrhizal fungi - Xin-Ping An; Abeer Hashem; Fábio Sérgio Barbosa da Silva; Qiang-Sheng Wu (Rhizosphere, 2025)

Unveiling non-radical oxidation pathways in peroxymonosulfate/cobalt(II) systems: Critical role of cobalt(III) and cobalt(IV) explored by manganese(II) probing - Luwei Li; Xuecong Qian; Shilong Wang; Yun Liu; Da Wang; Huixin Zhang; Yechen An; Haijun Cheng; Jun Ma (Journal of Hazardous Materials, 2025)

Polymer semiconductor-coated 3D bilayer cellulose nanofiber/polydimethylsiloxane aerogel for enhanced solar-driven interfacial water evaporation - Keerthnasre Dhandapani; Gayoung Ham; Hossein Fattahimoghaddam; In Ho Kim; Hyojung Cha; Xiaowu Tang; Da Wan Kim; Tae Kyu An; Yong Jin Jeong (Desalination, 2025)

High-precision age constraint for the Xiyingzi Bed of the Jiufotang Formation in western Liaoning, Northeast China - Li-Jun Zhang; Si-Yu Song; Shu-An Ji; Su-Chin Chang; Jahandar Ramezani; Fei Gao; Bo Wang; Hai-Chun Zhang; Da-Ran Zheng (Palaeoworld, 2025)

Influence of AC supply modes with different levels of energy sufficiency on cooling energy consumption in urban residential buildings - Wenyi Wei; Yi Wu; Jinjing Zhao; Da Yan; Jingjing An; Xin Zhou (Energy and Buildings, 2025)

Phosphoproteomics reveals essential regulatory roles of phosphorylation in marine oligotrophic bacteria - Yu Zhang; Yao-Hui He; Zhang-Xian Xie; Zhuo-An Bai; Guo-Sheng Hu; Ming-Hua Wang; Stephen J. Giovannoni; Da-Zhi Wang (Marine Life Science & Technology, 2025)
Oligotrophic bacteria with reduced genomes have relatively few transcriptional regulators and are thought to rely more than other bacteria on post-transcriptional regulation to respond to environmental stimuli. SAR11 bacteria are the most abundant group of heterotrophic bacteria in marine planktonic systems and are a model for understanding genome reduction in other free-living microorganisms. Here, we report a comprehensive, quantitative protein phosphorylation profile for SAR11 strain HTCC1062 grown under various environmentally relevant conditions, including light/dark cycles, temperature differences, and nutrient limitations, to investigate phosphorylation dynamics in this streamlined organism. Nearly half of proteins encoded by the genome were detected in phosphorylated forms under at least one condition. 1014 Ser/Thr/Tyr phosphorylation sites were observed in 1576 phosphopeptides from 555 phosphoproteins. Protein phosphorylation was concentrated in proteins for functions associated with nutrient acquisition and growth, such as ABC transporters, RNA polymerase, and ribosomal proteins. Prominent patterns in protein phosphorylation were detected across a range of culture conditions. In these cells, which previously have been shown to continuously express nearly their entire proteome, protein phosphorylation was more dynamic than protein abundance, supporting the hypothesis that post-transcriptional regulation by protein phosphorylation might play a large role in modulating protein activity. Our findings support a regulatory model characterized by minimal variation in protein expression but extensive protein phosphorylation. This model diverges from bacterial regulatory paradigms reliant on transcriptional control, and may be relevant to understanding other abundant heterotrophs with reduced genomes.

Simulation analysis on synergistic energy-saving effect of building envelope insulation and radiative cooling technology - Han Li; Jingjing An; Chuang Wang; Da Yan (Energy and Buildings, 2025)

Identification of novel sulfur-containing petroporphyrins in a natural bitumen: Potential biomarkers for aerobic organisms - Fang Zheng; Weisheng Yang; Yanbin Wang; Mi An; Da Huo; Chunyan Wang; Qing Cao; Jing He; Quan Shi; Yongge Sun (Organic Geochemistry, 2025)

Modulating energy band structure of CsPbBr3@TiO2 composites for enhanced photocatalytic and anti-superbacterial performance - Chang-Yeon Kim; Min-Gi Jeon; Artavazd Kirakosyan; Da-Hye Kim; Hea-Jong Chung; Ji-Hyun Lee; Ha-Rim An; Byoungchul Son; Seung Jo Yoo; Sang-Gil Lee; Ji-In Park; Soo Hyeon Kim; et al. (Journal of Water Process Engineering, 2025)

Geochemistry, geochronology and Fe-Mg-S isotopic composition of the Liaoshang gold deposit, Jiaodong Peninsula, China: Implications for ore-forming processes and mineral exploration - Yuan-lin Chen; Huan Li; Shang-yi Gu; Scott A. Whattam; Chao-yang Zheng; Li-gong Wang; Da-dou Li; Liu-an Duan (Journal of Geochemical Exploration, 2025)

Dietary exposure to environmental phenols and phthalates in Korean adults: data analysis of the Korean National Environmental Health Survey (KoNEHS) 2018–2020 - Lita Kim; Da-An Huh; Kangyeon Park; Jiyoun Lee; Se-Hyun Hwang; Hyeon Jeong Choi; Woohyun Lim; Kyong Whan Moon (International Journal of Hygiene and Environmental Health, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Enhancing drying efficiency and physicochemical & antioxidant properties of germinated brown rice through microwave incorporation - Xiaoyu Tie; Nannan An; Da Huo; Lina Wan; Dong Li; Dan Zhao; Lijun Wang; Yong Wang (Journal of Cereal Science, 2025)

Per- and polyfluoroalkyl substances exposures are associated with non-alcoholic fatty liver disease, particularly fibrosis - Se-Hyun Hwang; Yun-Hee Choi; Da-An Huh; Lita Kim; Kangyeon Park; Jiyoun Lee; Hyeon Jeong Choi; Woohyun Lim; Kyong Whan Moon (Environmental Pollution, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Tree-level carbon stock estimations across diverse species using multi-source remote sensing integration - Qing Li; Jia Yin; Xiaoxin Zhang; Dalei Hao; Matheus Pinheiro Ferreira; Wenhui Yan; Ye Tian; Da Zhang; Shen Tan; Sheng Nie; Tianyu An; Xiaoyao Li; et al. (Computers and Electronics in Agriculture, 2025)

Beyond traditional uses: the multifaceted bioactivities of steroidal saponins from the genus Trillium and their modern applications - Dong-Sheng Fan; Lu Yu; Xiao-Gang Zhou; Yue Zhang; Dong Yi; Qi-Bing Mei; Da-Lian Qin; Jian-Ming Wu; An-Guo Wu (Phytochemistry Reviews, 2025)

Unprecedented short-circuit current density and efficiency of vacuum-deposited organic solar cells based on 8H-thieno[2′,3′:4,5]thieno[3,2-b] thieno[2,3-d]pyrrole - Bin-Wen Chen; Ming-Wei An; Kang Wang; Sang Young Jeong; Xu Wang; Zhen-Lin Qiu; Kun Cao; Shan-Yu Zheng; Lu Wang; Han Young Woo; Da-Qin Yun; Lin-Long Deng; et al. (Science Bulletin, 2025)

A Hybrid-Surrogate-Calibration-Assisted Multi-Fidelity Modeling Approach and Its Application in Strength Prediction for Underwater Gliders - Chengshan Li; Yufan Cao; Xiaoyi An; Da Lyu; Junxiao Liu (Journal of Marine Science and Engineering, 2025)
Multi-fidelity surrogate-based methods play an important role in modern engineering design applications, aiming to improve model accuracy while reducing computational cost. One of the widely adopted approaches is the calibration-based method, which calibrates the low-fidelity model through a discrepancy model between low-fidelity and high-fidelity models. Since discrepancies between models exhibit varying characteristics across different problems, using a single surrogate for discrepancy approximation may lack stability. In practical engineering design problems, it is often hard for designers to select optimal surrogate models. To this end, a hybrid-surrogate-calibration-assisted multi-fidelity modeling (HSC-MFM) approach is proposed in this paper. Specifically, this approach integrates three representative surrogate models, including the polynomial response surface, Kriging model, and radial basis function, to comprehensively capture the discrepancy characteristics between different fidelity models. Furthermore, an adaptive weight calculation method is developed to improve the modeling accuracy. Testing results demonstrate that HSC-MFM achieves enhanced stability compared to most existing methods while maintaining good prediction accuracy. Finally, the proposed method is applied to predict the strength of the frame for a blended-wing-body underwater glider, which verifies its engineering applicability.

In vivo self-assembled bispecific fluorescence probe for early detection of bladder cancer and metastasis - Da-Yong Hou; Ni-Yuan Zhang; Peng Zhang; Xiang-Peng Li; Jiong-Cheng Wu; Mei-Yu Lv; Zhi-Jia Wang; Xing-Jie Hu; Jian-Xiao Liang; Hong-Lei Wang; Yue-Ze Wang; Hui-Hui You; et al. (Science Bulletin, 2025)

Equilibrium boron isotope fractionation during kaolinite adsorption and applications to chemical weathering processes - Yin-Chuan Li; Ya-Ru Zhou; Hai-Zhen Wei; Martin R. Palmer; Fa-Yang Guo; Yong-Hui Li; Yong-An Qi; Da-Ping Xia (Geochimica et Cosmochimica Acta, 2025)

Enhancing indoor air quality and cardiopulmonary health in patients with asthma by photocatalytic oxidation and filters air cleaner - Jia Lin Zhang; Guan-Yu Liao; Hong-Yi Lin; Jie-An Xie; Wan-Chen Li; Huang-Chi Chen; Da Wei Wu; Huai-Lei Juan; Jia-Yu Kuo; Pei-Shih Chen (Journal of Hazardous Materials, 2025)

Evaluation of acute, repeated dose 28-day and 13-week oral toxicity and genotoxicity of a standardized fraction (HemoHIM) from Angelica gigas, Cnidium officinale, and Paeonia lactiflora - Ju Gyeong Kim; Su-Bin Bak; Gyoung-Deuck Kim; Han-Sol Choi; Da-Ae Kwon; Ha-Young Kim; Dong-Won Son; Jang-Hun Jeong; Byung-Woo Lee; Hyo-Jin An; Hak Sung Lee (Toxicological Research, 2025)
HemoHIM is a functional food ingredient comprising a triple herbal combination of extracts from Angelica gigas Nakai, Cnidium officinale Makino, and Paeonia lactiflora Pallas. It was developed to aid the recovery of impaired immune function. Although it is widely used to treat various immune disorders in Korea, its potential toxicity has not been extensively investigated. Therefore, a comprehensive study was conducted to assess the safety of HemoHIM, including acute oral dose toxicity, 28-day and 13-week repeated-dose toxicity, and genotoxicity. To evaluate its safety profile, the dose was increased to 2,000 mg/kg/day, which corresponds to the dose limit for acute toxicity as per the Organization for Economic Cooperation and Development Test Guideline 423. No abnormal findings were observed at the higher doses. For the 28-day and 13-week repeated-dose toxicity studies, HemoHIM was administered at doses of 500, 1,000, and 2,000 mg/kg/day to examine subchronic toxicity in male and female rats. No test item-related clinical signs or mortality was observed at any of the tested doses. Gross pathology, hematology, blood chemistry, and histopathology evaluations further supported the safety of HemoHIM. Therefore, the NOAEL of HemoHIM was considered to be at 2,000 mg/kg/day for both sexes of rats. Bacterial reverse mutation tests, a chromosome aberration test in human peripheral blood lymphocytes, and a mouse micronucleus test were conducted to determine the genotoxicity of HemoHIM, which revealed that HemoHIM was non-mutagenic and non-clastogenic. Collectively, these findings provide valuable evidence to support the safe use of HemoHIM as a functional food ingredient.

Productivity experienced a more rapid enhancement trend than greenness across the Tibetan Plateau - Ruzhi An; Huaan Jin; Hui Zhao; Da Wei; Wei Zhao; Xiaodan Wang (Science of The Total Environment, 2024)

Unveiling the release mechanism of potentially toxic elements from Pb/Zn smelter contaminated soils under the coupled effects of freeze–thaw and acidification: Insights from mineralogical analysis - Da–Mao Xu; Bai–Hong An; Shao–Jun Jiang; Dong–Sheng Dai; Ze–Lin Xu; Lai Zhou; Xue–Qiang Zhu; Hong Yang; Rong–Bing Fu (Journal of Hazardous Materials, 2024)

Microfluidic-blow-spinning of carvacrol-loaded porphyrin metal − organic framework nanofiber films with synergistic antibacterial capabilities for food packaging - Zi-An Deng; Menglu Wu; Chaoyi Shen; Xiangzheng Yang; Da Wang; Jiangkuo Li; Di Wu; Kunsong Chen (Food Chemistry, 2024)

Bilinear Perceptual Fusion Algorithm Based on Brain Functional and Structural Data for ASD Diagnosis and Regions of Interest Identification - Jinxiong Fang; Da-fang Zhang; Kun Xie; Luyun Xu; Xia-an Bi (Interdisciplinary Sciences: Computational Life Sciences, 2024)

A Kriging-based method for calibrating the bonded-particle model parameters of iron ore - Haoyan Zhang; Shuai Wang; Yang An; Yukuan Wang; Shuwei Wu; Da Cui; Guoqiang Wang (Minerals Engineering, 2024)

Soil benzene emissions and inhalation health risks affected by various land covers - Ying Wang; Xuemin Ma; Yue Wang; Da An; Jianchao Zhu (Chemosphere, 2024)

A novel quantitative method of heatwave classification for building resilience analysis - Xue Liu; Zhaoru Liu; Yi Wu; Shan Hu; Fan Bu; Jingjing An; Xin Zhou; Da Yan (Sustainable Cities and Society, 2024)

Gut antibiotic resistome during pregnancy associates with the risk of gestational diabetes mellitus: New evidence from a prospective nested case−control study - Jing Li; Zhonghan Sun; Fengjiang Sun; Yuwei Lai; Xinzhu Yi; Zhang Wang; Jiaying Yuan; Yayi Hu; An Pan; Xiong-Fei Pan; Yan Zheng; Da Chen (Journal of Hazardous Materials, 2024)

Array-optimized artificial olfactory sensor enabling cost-effective and non-destructive detection of mycotoxin-contaminated maize - Maozhen Qu; Yingchao He; Weidong Xu; Da Liu; Changqing An; Shanming Liu; Guang Liu; Fang Cheng (Food Chemistry, 2024)

Deviation entropy-based dynamic multi-model ensemble interval prediction method for quantifying uncertainty of building cooling load - Changcheng Chen; Jingjing An; Xin Zhou; Chuang Wang; Han Li; Da Yan (Energy and Buildings, 2024)

Status and trends in the stability of the three largest ice shelves in Antarctica - Rongxing Li; Guojun Li; Lu An; Menglian Xia; Da Lv; Yuan Cheng; Aiguo Zhao; Tian Chang; Xiangbin Cui; Shengkai Zhang; Shijie Liu; Yixiang Tian; et al. (Science China Earth Sciences, 2024)

Marinobacter sediminicola sp. nov. and Marinobacter xiaoshiensis sp. nov., Isolated from Coastal Sediment - Jing An; Run-Yuan Mao; Shu-Xin Wang; Jing Zhang; Zong-Jun Du; Da-Shuai Mu (Current Microbiology, 2024)

Numerical study on the coupling effect of river attributes and riverside building forms on the urban microclimate: A case study in Nanjing, China - Yuxie Zhou; Yuxin Lu; Xin Zhou; Jingjing An; Da Yan (Sustainable Cities and Society, 2024)

A novel shadow calculation approach based on multithreaded parallel computing - Xin Zhou; Xiaohan Shen; Zhaoru Liu; Hongsan Sun; Jingjing An; Da Yan (Energy and Buildings, 2024)

Losing Tidal Flats at the Midpoint of the East Asian-Australasian Flyway over the past 100 Years - Wan-Jyun Chen; An-Yu Chang; Chia-Chi Lin; Ruey-Shing Lin; Da-Li Lin; Pei-Fen Lee (Wetlands, 2024)
The ecosystem services and functions of tidal flats have been overlooked for many decades, and tidal flat loss has been identified as a serious threat to many taxa in recent years, especially for migratory waterbirds. Despite the understanding of tidal flats change on the global scale, there are still a lot of unknowns on the small scale, including tidal flats in Taiwan, which are important stopover sites for migratory waterbirds along the East Asian–Australasian Flyway. Therefore, we collated historic topographic maps, Landsat Archive images between the 1920s and the 2020s to determine the trajectories of tidal flat change along the coastline of Taiwan. Our results show that tidal flat coverage expanded between the 1920s and the 1950s, but lost approximately 266 km 2 (58%) between the 1950s and the 2010s. The status of the tidal flats along the western coastline of Taiwan has been identified as “Endangered” based on the criteria of the IUCN Red List of Ecosystems. According to the aims of the Global Biodiversity Framework, we suggest rethinking the land use plans along the coastline to mitigate the tidal flat loss, especially the controversial issues concerning the expansion of green energy infrastructure. To realize the Nature Positive goals by 2030, recovering and restoring the tidal flat ecosystem could be one of the key strategies.

Health risks of pest control and disinfection workers after the COVID-19 outbreak in South Korea - Yun-Hee Choi; Da-An Huh; Lita Kim; Sang ji Lee; Kyong Whan Moon (Journal of Environmental Sciences, 2024)

The simultaneous removal of methylene blue (MB) and Ca2+ by recyclable adsorbents based the scales derived from coal gasification system - Bai-Hong An; Da-Mao Xu; Run-Ting Wang; Ye-Xuan Wen; Rui Geng; Jia-Yun Wu; Xian-Chun Tang; Hong-Bin Chen (Environmental Science and Pollution Research, 2024)

Thalassinoides ichnofabrics from the Zhangxia Formation (Cambiran Miaolingian series) in Henan province: Bioturbators as Ecosystem engineers - Bingchen Liu; Yong'an Qi; Min Wang; Wenyi He; Yaogang Du; Da Li; Mingyue Dai (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Evaluation of acute, 28-day, 13-week repeated dose oral toxicity and genotoxicity of a herbal extract (HemoHIM G) from Angelica sinensis, Ligusticum chuanxiong, and Peaonia lactiflora - Su-Bin Bak; Hansol Choi; Gyoung-Deuck Kim; Ju Gyeong Kim; Da-Ae Kwon; Ha-Young Kim; Dong-Won Son; Jang-Hun Jeong; Byung-Woo Lee; Hyo-Jin An; Hak Sung Lee (Toxicological Research, 2024)
HemoHIM G is a functional food ingredient composed of a triple herbal combination of Angelica sinensis , Ligusticum chuanxiong , and Paeonia lactiflora , to improve impaired immune function. Considering the pharmacological benefits of its constituent herbal components, HemoHIM G is anticipated to have various health benefits; however, its toxicity has not been thoroughly evaluated. Here, we conducted a comprehensive study to assess the safety of HemoHIM G in terms of acute oral toxicity, 13-week repeat-dose toxicity, and genotoxicity. In the oral acute toxicity study, Sprague–Dawley rats were orally administered a single dose of HemoHIM G at 5000 mg/kg/day, the limit dose for the acute study. No abnormal findings or adverse effects were observed in this study, as confirmed by gross pathology. A 13-week repeated-dose toxicity study was conducted with HemoHIM G at doses of 1250, 2500, and 5000 mg/kg/day to examine the subchronic toxicity in both male and female rats after 28 days of dose-range finding study. No test substance-related clinical signs or mortality was observed at any of the tested doses. Gross pathology, hematology, blood chemistry, and histopathology were within normal ranges, further supporting the safety of HemoHIM G. Therefore, the NOAEL of HemoHIM G was considered to be at 5000 mg/kg/day for both sexes of rats. Bacterial reverse mutation tests, a chromosome aberration test in human peripheral blood lymphocytes, and a mouse micronuclei test were conducted to identify the potential genotoxicity of HemoHIM G. HemoHIM G is non-mutagenic and non-clastogenic. Collectively, these findings provide valuable evidence for the safe use of HemoHIM G as a functional food ingredient.

Association between oil spill clean-up work and thyroid cancer: Nine years of follow-up after the Hebei Spirit oil spill accident - Yun-Hee Choi; Lita Kim; Da-An Huh; Kyong Whan Moon; Min-Sung Kang; Yong-Jin Lee (Marine Pollution Bulletin, 2024)

Long-term effects of the Hebei Spirit oil spill on the prevalence and incidence of allergic disorders - Se Hyun Hwang; Yong-Jin Lee; Yun-Hee Choi; Da-An Huh; Min-Sung Kang; Kyong Whan Moon (Science of The Total Environment, 2024)

A novel physical-feature-based approach for stochastic simulation of typical building electricity use profiles - Xuyuan Kang; Xiao Wang; Jingjing An; Xue Liu; Da Yan (Energy and Buildings, 2024)

Key parameters and mechanisms of ice cores autonomously breaking with air reverse-circulation drill systems - Rusheng Wang; Xinyu Lv; Xiaopeng Fan; Da Gong; An Liu (Cold Regions Science and Technology, 2024)

Reinforcement learning approach for optimal control of ice-based thermal energy storage (TES) systems in commercial buildings - Xiao Wang; Xuyuan Kang; Jingjing An; Hanran Chen; Da Yan (Energy and Buildings, 2023)

Acceleration of state–space method based on parallelization for enhancing building thermal process simulation efficiency - Fan Bu; Xuyuan Kang; Da Yan; Ruhong Wu; Hongsan Sun; Jingjing An; Xiao Wang (Energy and Buildings, 2023)

Indicator of climate variability: low treeline displacement in arid valleys of mountain areas, China - Wei-po Yan; Qing Wang; Ya-lin Guo; Qi Hu; Min Yang; Yi-da An (Journal of Mountain Science, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

A novel approach to examining the optimal use of the cooling effect of water bodies in urban planning - Zehongyu Kang; Hua Liu; Yuxin Lu; Xinyu Yang; Xin Zhou; Jingjing An; Da Yan; Xing Jin; Xing Shi (Building and Environment, 2023)

Systemic lupus erythematosus with high disease activity identification based on machine learning - Da-Cheng Wang; Wang-Dong Xu; Zhen Qin; Lu Fu; You-Yu Lan; Xiao-Yan Liu; An-Fang Huang (Inflammation Research, 2023)

Phthalate exposure with sperm quality among healthy Chinese male adults: The role of sperm cellular function - Pan Yang; Lang-Jing Deng; Jin-Ying Xie; Xiao-Jie Li; Xiao-Na Wang; Bin Sun; Tian-Qing Meng; Cheng-Liang Xiong; Yi-Chao Huang; Yi-Xin Wang; An Pan; Da Chen; et al. (Environmental Pollution, 2023)

Preparation of carbon foam from depolymerization-reforming lignin for capacitive deionization - Chun-Ping Li; Ya-Qi Wu; Jia-Jia An; Li-Xin Gao; Da-Quan Zhang; Jin Li; Zhong-Xun An (Desalination, 2023)

Water quality determines protist taxonomic and functional group composition in a high-altitude wetland of international importance - Ruizhi An; Yang Liu; Chengmei Pan; Zhen Da; Peng Zhang; Nanqian Qiao; Feng Zhao; Sang Ba (Science of The Total Environment, 2023)

Mechanistic insights into the migration behavior of cadmium (Cd) in the soil and groundwater systems at a construction site: Experimental and numerical analysis - Da–Mao Xu; Ze–Lin Xu; Zi–Qi Mu; Bai–Hong An; Xiao–Wen Fang; Rong–Bing Fu (Journal of Environmental Chemical Engineering, 2023)

Lupus nephritis or not? A simple and clinically friendly machine learning pipeline to help diagnosis of lupus nephritis - Da-Cheng Wang; Wang-Dong Xu; Shen-Nan Wang; Xiang Wang; Wei Leng; Lu Fu; Xiao-Yan Liu; Zhen Qin; An-Fang Huang (Inflammation Research, 2023)

Effects of low salinity stress on osmoregulation and gill transcriptome in different populations of mud crab Scylla paramamosain - Wen-Bin Xu; Yan-Mei Zhang; Bang-Ze Li; Chen-Yang Lin; Da-Yong Chen; Yuan-Xin Cheng; Xiao-Ling Guo; Wei-Ren Dong; Miao-An Shu (Science of The Total Environment, 2023)

A systematic review of building electricity use profile models - Xuyuan Kang; Jingjing An; Da Yan (Energy and Buildings, 2023)

Ectopic expression of MmCYP1A1, a mouse cytochrome P450 gene, positively regulates stress tolerance in apple calli and Arabidopsis - Xiao-Na Wang; Fei Yang; Jiu-Cheng Zhang; Yi-Ran Ren; Jian-Ping An; Da-Yong Chang; Xiao-Fei Wang; Chun-Xiang You (Plant Cell Reports, 2023)

The pretreatment effects of various target pollutant in real coal gasification gray water by coupling pulse electrocoagulation with chemical precipitation methods - Bai-Hong An; Da-Mao Xu; Rui Geng; Yan Cheng; Rui-Bo Qian; Xian-Chun Tang; Zhi-Qiang Fan; Hong-Bin Chen (Chemosphere, 2023)

Horticoccus luteus gen. nov., sp. nov., A Novel Member of the Phylum Verrucomicrobia Isolated from a Dichlorodiphenyltrichloroethane (DDT)-Contaminated Orchard Soil - Joon-hui Chung; Ja-Yeon Lee; Geun-Hyung Choi; Miyoung Won; Jehyeong Yeon; Younggun Yoon; Si-Hyun An; Da-Yeon Kim; InCheol Park; Ye-eun Kim; Jae-Hyung Ahn (Current Microbiology, 2022)

Robiginitalea marina sp. nov., isolated from coastal sediment - Xiao-Qi Xuan; Run-Yuan Mao; Wen-Xing Yu; Jing An; Zong-Jun Du; Da-Shuai Mu (Archives of Microbiology, 2022)

Piperock ichnofabrics from western Henan, China: spatial distribution pattern and environmental controls on middle Cambrian carbonates - Bingchen Liu; Da Li; Min Wang; Mingyue Dai; Wenyi He; Jingbo Li; Yong’an Qi (International Journal of Earth Sciences, 2022)

Influences of the 1855 AD Huanghe (Yellow River) Relocation on Sedimentary Organic Carbon Burial in the Southern Yellow Sea - Jianying Liu; Da-Wei Li; Yang Ding; Tiantian Ge; Weifang Chen; Chih-An Huh; Meixun Zhao (Frontiers in Marine Science, 2022)
The Huanghe (Yellow River) supplies large amount of sediments and terrestrial organic carbon (OC) to the eastern Chinese marginal seas. A relocation of the Huanghe outlet from the southern Yellow Sea (YS) to the Bohai Sea occurred in 1855 AD, however, detailed knowledge about the impact of this relocation on sedimentary source and OC burial in Chinese marginal seas is still critically lacking. In this study, we present total OC content and its isotope (δ 13 C), along with bulk total organic carbon (TOC)/total nitrogen (TN) molar ratio and lipid biomarker contents, in a sediment core HH12 from the southern YS with sediment age spanning the last 300 years. We find that TOC and terrestrial lipid biomarker mass accumulation rates were lower between 1855 AD and 1950 AD than that prior to 1855 AD in core HH12; and in accordance, both TOC/TN ratio and δ 13 C records indicate a gradual decrease of terrigenous source contributions to sedimentary OC. This suggests that the relocation of the Huanghe outlet reduced the transport of terrestrial OC to the southern YS. However, the δ 13 C record also indicates a relative increase of terrestrial OC contribution to sedimentary OC after 1950 AD, and the most likely explanation is increased contributions from the old Huanghe delta erosion and Korean rivers. Future studies should focus on better constraining the variations of terrestrial and marine endmembers with δ 13 C and Δ 14 C analyses of specific biomarkers to examine these linkages.

Alternation of stromatolites and vertical burrows controlled by storm processes and sea-level changes in the middle Cambrian carbonates of central China - Bingchen Liu; Mingyue Dai; Yong’an Qi; Xiaofang Sun; Wei Zheng; Min Wang; Zhifeng Xing; Da Li; Yuchao Fan (Journal of Earth System Science, 2022)

Rapid visual detection of porcine reproductive and respiratory syndrome virus via recombinase polymerase amplification combined with a lateral flow dipstick - Xiao-Xiao Tian; Tao Wang; Xing-Yang Cui; Xin-Yi Huang; Yue Sun; Da-Song Xia; Yong-Bo Yang; Xue-Hui Cai; Tong-Qing An (Archives of Virology, 2022)

Investigation on the statistical characteristics of geoelectric field seismic anomalies in the North–South seismic belt of Chinese mainland - Hou Ze-Yu; An Zhang-Hui; Fan Ying-Ying; Tan Da-Cheng; Fu A-Long; Wei Lei (Acta Geophysica, 2021)

Resting-state abnormalities in functional connectivity of the default mode network in autism spectrum disorder: a meta-analysis - Qing Wang; Hua-Yun Li; Yun-Da Li; Ya-Ting Lv; Hui-Bin Ma; An-Feng Xiang; Xi-Ze Jia; Dong-Qiang Liu (Brain Imaging and Behavior, 2021)

Summary of technology for a comprehensive geophysical exploration of gold mine in North China Craton - Qingyun Di; Guoqiang Xue; Da Lei; Qingdong Zeng; Changmin Fu; Zhiguo An (Science China Earth Sciences, 2021)

Microbiogenic thrombolites from the Cambrian Miaolingian Series of southern North China Craton - Xiaofang Sun; Mingyue Dai; Yong’an Qi; Bingchen Liu; Wei Zheng; Zhifeng Xing; Min Wang; Da Li; Yuchao Fan (Carbonates and Evaporites, 2021)

Investigation on Hydrodynamic Performance of Flapping Foil Interacting with Oncoming Von Kármán Wake of a D-Section Cylinder - Jian Li; Peng Wang; Xiaoyi An; Da Lyu; Ruixuan He; Baoshou Zhang (Journal of Marine Science and Engineering, 2021)
Flapping foils are studied to achieve an efficient propeller. The performance of the flapping foil is influenced by many factors such as oncoming vortices, heaving amplitude, and geometrical parameters. In this paper, investigations are performed on flapping foils to assess its performance in the wake of a D-section cylinder located half a diameter in front of the foil. The effects of heaving amplitude and foil thickness are examined. The results indicate that oncoming vortices facilitate the flapping motion. Although the thrust increases with the increasing heaving amplitude, the propelling efficiency decreases with it. Moreover, increasing thickness results in higher efficiency. The highest propelling efficiency is achieved when the heaving amplitude equals ten percent of the chord length with a symmetric foil type of NACA0050 foil. When the heaving amplitude is small, the influence of the thickness tends to be more remarkable. The propelling efficiency exceeds 100% and the heaving amplitude is 10% of the chord length when the commonly used equation is adopted. This result demonstrates that the flapping motion extracts some energy from the oncoming vortices. Based on the numerical results, a new parameter, the energy transforming ratio (RET), is applied to explicate the energy transforming procedure. The RET represents that the flapping foil is driven by the engine or both the engines and the oncoming vortices with the range of RET being (0, Infini) and (−1, 0), respectively. With what has been discussed in this paper, the oncoming wake of the D-section cylinder benefits the flapping motion which indicates that the macro underwater vehicle performs better following a bluff body.

Intracutaneous Delivery of Gelatins Reduces Fat Accumulation in Subcutaneous Adipose Tissue - Sung-Min An; Min Jae Kim; Keum-Yong Seong; Jea Sic Jeong; Hyeon-Gu Kang; So Young Kim; Da Som Kim; Da Hee Kang; Seung Yun Yang; Beum-Soo An (Toxicological Research, 2019)

Coring of Antarctic Subglacial Sediments - Da Gong; Xiaopeng Fan; Yazhou Li; Bing Li; Nan Zhang; Raphael Gromig; Emma C. Smith; Wolf Dummann; Sophie Berger; Olaf Eisen; Jan Tell; Boris K. Biskaborn; et al. (Journal of Marine Science and Engineering, 2019)
Coring sediments in subglacial aquatic environments offers unique opportunities for research on paleo-environments and paleo-climates because it can provide data from periods even earlier than ice cores, as well as the overlying ice histories, interactions between ice and the water system, life forms in extreme habitats, sedimentology, and stratigraphy. However, retrieving sediment cores from a subglacial environment faces more difficulties than sediment coring in oceans and lakes, resulting in low yields from the most current subglacial sediment coring methods. The coring tools should pass through a hot water-drilled access borehole, then the water column, to reach the sediment layers. The access boreholes are size-limited by the hot water drilling tools and techniques. These holes are drilled through ice up to 3000–4000 m thick, with diameters ranging from 10–60 cm, and with a refreezing closure rate of up to 6 mm/h after being drilled. Several purpose-built streamline corers have been developed to pass through access boreholes and collect the sediment core. The main coring objectives are as follows: (i) To obtain undisturbed water–sediment cores, either singly or as multi-cores and (ii) to obtain long cores with minimal stratigraphic deformation. Subglacial sediment coring methods use similar tools to those used in lake and ocean coring. These methods include the following: Gravity coring, push coring, piston coring, hammer or percussion coring, vibrocoring, and composite methods. Several core length records have been attained by different coring methods, including a 290 cm percussion core from the sub-ice-shelf seafloor, a 400 cm piston core from the sub-ice-stream, and a 170 cm gravity core from a subglacial lake. There are also several undisturbed water–sediment cores that have been obtained by gravity corers or hammer corers. Most current coring tools are deployed by winch and cable facilities on the ice surface. There are three main limitations for obtaining long sediment cores which determines coring tool development, as follows: Hot-water borehole radial size restriction, the sedimentary structure, and the coring techniques. In this paper, we provide a general view on current developments in coring tools, including the working principles, corer characteristics, operational methods, coring site locations, field conditions, coring results, and possible technical improvements. Future prospects in corer design and development are also discussed.

Seasonal cycle of the salinity barrier layer revealed in the northeastern Gulf of Guinea - AN Dossa; CY Da-Allada; G Herbert; B Bourlès (African Journal of Marine Science, 2019)

The Contributions of Climate Changes and Human Activities to Long-Term Variations in Lake Sediments Based on Results from Generalized Additive Models - Zhuoshi He; Shouliang Huo; Chunzi Ma; Hanxiao Zhang; Da An; Beidou Xi; Qiujing Xu; Xinghui Xia; Fengchang Wu (Water Resources Management, 2019)

An ensemble-based likelihood ratio approach for family-based genomic risk prediction - Hui An; Chang-shuai Wei; Oliver Wang; Da-hui Wang; Liang-wen Xu; Qing Lu; Cheng-yin Ye (Journal of Zhejiang University-SCIENCE B, 2018)

Investigation of the anisotropy of black shale in dynamic tensile strength - Xiaoshan Shi; Da’an Liu; Wei Yao; Yirui Shi; Tiewu Tang; Bonan Wang; Weige Han (Arabian Journal of Geosciences, 2018)

Risk-Based Prioritization Method for the Classification of Groundwater Pollution from Hazardous Waste Landfills - Yu Yang; Yong-Hai Jiang; Xin-Ying lian; Bei-Dou Xi; Zhi-fei Ma; Xiang-Jian Xu; Da An (Environmental Management, 2016)

Stochastic finite modeling of ground motion for March 5, 2012, Mw 4.6 earthquake and scenario greater magnitude earthquake in the proximity of Delhi - Himanshu Mittal; Yih-Min Wu; Da-Yi Chen; Wei-An Chao (Natural Hazards, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Applications of Computer Vision for Assessing Quality of Agri-food Products: A Review of Recent Research Advances - Ji Ma; Da-Wen Sun; Jia-Huan Qu; Dan Liu; Hongbin Pu; Wen-Hong Gao; Xin-An Zeng (Critical Reviews in Food Science and Nutrition, 2016)

Applications of Near-infrared Spectroscopy in Food Safety Evaluation and Control: A Review of Recent Research Advances - Jia-Huan Qu; Dan Liu; Jun-Hu Cheng; Da-Wen Sun; Ji Ma; Hongbin Pu; Xin-An Zeng (Critical Reviews in Food Science and Nutrition, 2015)

Recent Developments and Applications of Hyperspectral Imaging for Quality Evaluation of Agricultural Products: A Review - Dan Liu; Xin-An Zeng; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2015)

Benzo(a)pyrene represses melanogenesis in B16F10 mouse melanoma cells - Da Hye Joo; Hwa Jun Cha; Karam Kim; Minhee Jung; Jung Min Ko; In Sook An; Sung Nae Lee; Hyun Hee Jang; Seunghee Bae; Nam Kyung Roh; Kyu Joong Ahn; Sungkwan An (Molecular & Cellular Toxicology, 2015)

Advances in Feature Selection Methods for Hyperspectral Image Processing in Food Industry Applications: A Review - Qiong Dai; Jun-Hu Cheng; Da-Wen Sun; Xin-An Zeng (Critical Reviews in Food Science and Nutrition, 2015)

Research Developments in Methods to Reduce the Carbon Footprint of the Food System: A Review - Zhongyue Xu; Da-Wen Sun; Xin-An Zeng; Dan Liu; Hongbin Pu (Critical Reviews in Food Science and Nutrition, 2015)

Applications of Hyperspectral Imaging in Chicken Meat Safety and Quality Detection and Evaluation: A Review - Zhenjie Xiong; Anguo Xie; Da-Wen Sun; Xin-An Zeng; Dan Liu (Critical Reviews in Food Science and Nutrition, 2015)

Recent Advances in Methods and Techniques for Freshness Quality Determination and Evaluation of Fish and Fish Fillets: A Review - Jun-Hu Cheng; Da-Wen Sun; Xin-An Zeng; Dan Liu (Critical Reviews in Food Science and Nutrition, 2015)

Strain Rate Dependency of Coarse Crystal Marble Under Uniaxial Compression: Strength, Deformation and Strain Energy - Yanrong Li; Da Huang; Xi’an Li (Rock Mechanics and Rock Engineering, 2014)

Influence of dip directions on the main deformation region of layered rock around tunnels - Zhen-dong Cui; Da-an Liu; Fa-quan Wu (Bulletin of Engineering Geology and the Environment, 2014)

Analysis for remedial alternatives of unregulated municipal solid waste landfills leachate-contaminated groundwater - Da An; Yonghai Jiang; Beidou Xi; Zhifei Ma; Yu Yang; Queping Yang; Mingxiao Li; Jinbao Zhang; Shunguo Bai; Lei Jiang (Frontiers of Earth Science, 2013)

Evaluation of landslide risk based on synchronization of nonlinear motions in observed data - Da-Chao Lin; Jing-Luo Cai; Zhang-Lin Guo; Fan-Lei Zeng; Feng-Ping An; Hai-Bo Liu (Natural Hazards, 2013)

Functional analysis of Waardenburg syndrome-associated PAX3 and SOX10 mutations: report of a dominant-negative SOX10 mutation in Waardenburg syndrome type II - Hua Zhang; Hongsheng Chen; Hunjin Luo; Jing An; Lin Sun; Lingyun Mei; Chufeng He; Lu Jiang; Wen Jiang; Kun Xia; Jia-Da Li; Yong Feng (Human Genetics, 2012)

Mitochondrial DNA diversity of Glyptothorax zanaensis (Wu et al., 1981) populations in Nu River, China - Xi-Ping Yuan; Yuan-An Wu; Bo Hong; Deng-Qiang Wang; Shao-Ping Liu; Da-Qing Chen (Environmental Biology of Fishes, 2012)

Amino Acid Homochirality may be Linked to the Origin of Phosphate-Based Life - Da Xiong Han; Hai Yan Wang; Zhi Liang Ji; An Fu Hu; Yu Fen Zhao (Journal of Molecular Evolution, 2010)

Flexible design of a rock slope abutment at the Wuqiangxi Hydroelectric Power Station - Yanjun Shang; Hyeong-Dong Park; Zhifa Yang; Da’an Liu; Chunhua Tang (Bulletin of Engineering Geology and the Environment, 2006)

Escape of atmospheric gases from the Moon - Da Dao-an; Yang Ya-tian (Journal of Earth System Science, 2005)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)